Performance enhancement of selective layer coated on solar absorber panel with reflector for water heater by response surface method: A case study. (August 2022) - Ramesh, C.; Vijayakumar, M.; Alshahrani, Saad; Navaneethakrishnan, G.; Palanisamy, R.; L, Natrayan; Saleel, C Ahamed; Afzal, Asif; Shaik, Saboor; Panchal, Hitesh
Abstract: In solar thermal applications, the performance of a solar absorber panel with a reflector is critical. In sense, different absorbers are used to enhance thermal efficiency. In addition to this, various coatings on solar absorber panels are introduced, and the performance of the same coated panels are examined with experimental study by design of experiment concept. For the reason, this work utilized the black-chrome coating (BC) and nickel-cobalt-coating (Ni-Co) on copper solar absorber panel. The reflectors were also used to maximize the incident solar radiation on the absorber. In this experiment the process variables are flow rate, collector angle, and reflector angle and the thermal efficiency of solar panel is the response. The response surface methodology with Box Behnken design is used to collect the experimental data from experimental setup. The collected data from designed experiment are analyzed by using Analysis of Variance Table (ANOVA). From this the coating on the absorber panel and reflectors are improved the thermal efficiency up to 89.3% of the Black – Chrome solar flat plate collector than Ni-Co panel.